Ectopic expression of Drosophila ELAV and human HuD in Drosophila wing disc cells reveals functional distinctions and similarities. - Toba, G.; Qui, J.; Koushika, S.P.; White, K. (Journal of Cell Science, 2002)
Drosophila ELAV and human HuD are two neuronal RNA binding proteins that show remarkable sequence homology, yet differ in their respective documented roles in post-transcriptional regulation. ELAV regulates neural-specific alternative splicing of specific transcripts, and HuD stabilizes specific mRNAs that are otherwise unstable due to AU-rich elements (AREs) in their 3' untranslated region (UTR). AREs are major determinants of transcript stability in mammalian cells. The role of each of these proteins was investigated and compared, by ectopically expressing them in Drosophila imaginal wing disc cells, which lack endogenous expression of either protein. The effect of the ectopic expression of ELAV and HuD was assessed on two sets of green fluorescent protein reporter transgenes, which were all driven with a broadly expressing promoter. Each set consisted of three reporter transgenes: (1) with an uninterrupted open reading frame (ORF); (2) with a constitutively spliced intron inserted into the ORF; and (3) with the intron nASI whose splicing is regulated in neurons by ELAV, inserted into the ORF. The two sets differed from each other only in their 3'UTR: Heat-shock-protein-70Ab (Hsp70Ab) trailer with ARE-like characteristics or Actin 5C (Act5C) trailer. Our results show that: (1) both ectopically expressed ELAV and HuD can enhance expression of transgenes with the Hsp70Ab 3'UTR, but not of transgenes with Act5C 3'UTR; (2) this enhancement is accompanied by an increase in mRNA level; (3) only ELAV can induce neural-specific splicing of nASI; and (4) although HuD is localized primarily to the cytoplasm, ELAV is localized to both the cytoplasm and the nucleus.